Case Study: Nursing Implementation of Deep Breathing Exercises in Cases of Violent Behavior - Anggita, Bella (International Journal Scientific and Professional, 2023)
Violent behavior is a response to stressors faced by a person, by carrying out acts of violent behavior, either towards oneself, other people or the environment, verbally or non-verbally. Acts of violent behavior aim to injure other people physically or psychologically, as seen in the behavior. actually committing violence. Clients need to receive treatment, namely implementation in the form of one implementation strategy for clients in the Cempaka room. This research uses a descriptive method in the form of a case study to explore the implementation of nursing deep breathing exercises in schizophrenic patients with violent behavior problems at the Ernaldi Bahar Hospital, South Sumatra Province. The subjects of this research were two patients, namely schizophrenic patients with violent behavior problems. Carried out for seven days on April 8-15 2021. The results of this study show that deep breathing exercises are effective in controlling violent behavior in schizophrenia patients..